CURRENT ISSUES OF MEDICAL STAFFING IN SURKHANDARYA REGION (1991–2000) (Western European Journal of Historical Events and Social Science, 2026)
This article analyzes the problems of providing the medical system with personnel in Surkhandarya region in the first decades of independence. The article shows the difficulties that arose in the process of providing medical institutions with qualified specialists, such as the geographical location of the region, the location of some regions in remote and remote areas, and the insufficient development of social infrastructure.